Educação no meio rural: um estudo sobre salas multisseriadas - Caroline Leite Rodrigues (2009)
The aim of this research is to understand the pedagogical practice of multi-graded classroom teachers, going through territories of teachers education who start to give their first steps towards the specificities of Rural Education and of multi-graded classrooms, with courses which contemplate the reality of country people, proposing to offer a kind of education which values their origins values, costumes, culture supplying the real needs related rural teachers education. Courses such as Pedagogia da Terra and the program Escola Ativa, which have differentiated pedagogical programs aiming an education for freedom, to form a person conscious of his social role. The multi-graded classrooms are labeled as a synonym of slowness and poor quality once they are made up of several grades with one only teacher, located usually in rural places, with precarious physical and material structure. However, we will see that the teaching in those classes can be of good quality, since a minimum condition of structure is offered. This research shows the changes, in these multi- graded schools along the years, regarding the teachers formation, school structure, teaching working conditions, school transportation, the emerging of the concept of Rural Education, among others. Therefore, theoretical background was searched in Tardif (2000, 2002, 2005), Pimenta (2005), Arroyo (2000, 2007), and others, who discuss the formation and practice of the teachers. Regarding the Rural Education there was the contribution of authors such as Caldart (2004, 2008, 2009), Calazans (1993), Molina (2008), Vendramini (2008), Leite (2002). The research was organized in six chapters, besides the introduction and the final considerations, where the pedagogical practice of multi-graded classroom teacher was analyzed, based on daily observation, interviews and questionnaires, which associated to theoretical referential led to the construction of this work which aims to understand how this practice is formed without an academic formation which has this teaching modality.